Brief communication: A magma depletion alternative for vent distribution in volcanic fields - Bebbington MS; Whitehead MG; Kereszturi G (Copernicus Publications for the European Geosciences Union, 2025)
The location of a volcanic vent controls an eruption’s hazards, intensities, and impact. Current kernel density estimation methods of future vent locations in volcanic fields assume that locations with more past-vents are more likely to produce future-vents. We examine an alternative hypothesis that an eruption depletes the magma source, causing holes or dips in the spatial density estimate for future vent locations. This is illustrated with the Auckland Volcanic Field, Aotearoa-New Zealand, where both magmatic and phreatomagmatic eruptions have occurred, according to the vent location, with the latter resulting in more explosive eruptions and hence hazard.